PENGEMBANGAN WEBSITE PROFIL DESA SALAMNNUNGGAL SEBAGAI MEDIA INFORMASI - Salsabila Sya’bania,; Fikri Amrullah,; Ayu Suniarti Febrianti,; Kokom Komala,; Taopik Arya Yasin Arachman, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The development of a village profile website is a strategic step in supporting transparency, efficiency of public services, and openness of information at the Salamnunggal Village Government level. Currently, the village does not have an official digital media platform to provide information to the community in an efficient and structured manner. This initiative aims to design and develop the Salamnunggal Village profile website as a platform for information dissemination and village data management. The methodology employed is the Community Service approach, which includes interviews, observations, and website application development methods, specifically the waterfall model. This involves analyzing needs through direct observations and interviews with Salamnunggal Village officials, as well as system testing using blackbox testing and system maintenance. The developed website features key elements such as village profiles, government structure, news, village potential, and SMEs. The website is also equipped with a Content Management System (CMS) to facilitate independent information management by administrators. With this website, it is hoped that transparency in information will be enhanced and Salamnunggal Village will be promoted in the digital world